Implementasi Sistem Informasi untuk Pemantauan dan Evaluasi Efektivitas E-Learning - Farida Nurlaila; Joko Riyanto; Fajar Agung Nugroho (Jurnal Informatika Universitas Pamulang, 2020)
This study discusses the monitoring and evaluation of e-learning activities through the LMS (Learning Management System) application of Pamulang University. In the previous process, the system used could only display activities carried out by lecturers that were recorded in the e-learning log. The logs that are displayed only create, update, delete activity, and cannot provide information about the effectiveness of online learning. Other parameters are needed to measure the effectiveness of online learning. One of them is the number of activities lecturers have to do for each subject within a certain period. In each course, the lecturer activity frequency is called create. Create is intended to open discussion topics by providing questions and responses to students' answers. From the results of monitoring, the achievement of creation is not sufficient to determine the success of implementing e-learning at Pamulang University. So that several other restrictions are needed such as participation, intensity, and content suitability. However, problems that occur in other parameters cannot be monitored just by looking at the data from the e-learning log. From these problems, a visual presentation of the activities of lecturers and students is needed which allows Study Programs with low percentages to be identified as quickly as possible, and decision making can be determined. The results showed that the four parameters can be implemented in the system. The average value of student participation in discussion forums is 74.99%, the ratio of the intensity of the activeness of lecturers and students every day of the week during the implementation period is 49.40%. Then the content suitability obtained an average of 0.04% and an average value of 65.90% lecturer activity. The generating facility automatically shows the four parameters in cooperation with the final result considered to assess the effectiveness of e-learning.